2020
DOI: 10.3390/ma13153420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Family Materials on Multiple Myeloma and Non-Hodgkin’s Lymphoma Cell Lines

Abstract: The interest around the graphene family of materials is constantly growing due to their potential application in biomedical fields. The effect of graphene and its derivatives on cells varies amongst studies depending on the cell and tissue type. Since the toxicity against non-adherent cell lines has barely been studied, we investigated the effect of graphene and two different graphene oxides against four multiple myeloma cell lines, namely KMS-12-BM, H929, U226, and MM.1S, as well as two non-Hodgkin lymphoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…A similar phenomenon has been observed by other authors in studies using in vitro cell cultures [ 5 , 8 , 46 ]. To observe the behavior of PG and GO in the in vitro conditions, HS-5 cells were exposed to increasing concentrations of nanomaterials (5–100 μg/mL) and their cellular viability was determined using XTT assay after 24 h. The viability of HS-5 cells decreased after administration of PG at concentrations of 20–100 μg/mL.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A similar phenomenon has been observed by other authors in studies using in vitro cell cultures [ 5 , 8 , 46 ]. To observe the behavior of PG and GO in the in vitro conditions, HS-5 cells were exposed to increasing concentrations of nanomaterials (5–100 μg/mL) and their cellular viability was determined using XTT assay after 24 h. The viability of HS-5 cells decreased after administration of PG at concentrations of 20–100 μg/mL.…”
Section: Resultssupporting
confidence: 89%
“…The growing biomedical field of applications of graphene-based materials raises questions regarding their toxicity. The interaction between dispersed GFM has been studied in vitro using human and animal cell cultures, such as HaCaT keratinocytes [ 2 ], human umbilical vein endothelial cells (HUVEC) [ 3 ], glioma cells [ 4 , 5 , 6 ], human multiple myeloma cells (RPMI-8226) [ 7 , 8 ], human mesenchymal stem cells (hMSCs) [ 9 ], red blood cells [ 10 ] and neuronal cells [ 11 ]. Many studies have shown that graphene toxicity depends on the size of the flakes.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of GO was evaluated in vitro in cellular models for adherent and nonadherent cell types and was reported to be low or moderate. Furthermore, GO (only particles of a small lateral size) increased the growth rate of the vascular smooth muscle cells while not affecting cell migration .…”
Section: Introductionmentioning
confidence: 99%